Successful Perioperative Management of Titanium Cranioplasty in a Patient with Severe Hemophilia A - Gabriela Micurova; Kristina Maria Belakova; Tomas Simurda; Miroslava Drotarova; Jan Stasko; Branislav Kolarovszki (Hemato, 2025)
Background: Hemophilia A is an X-linked recessive bleeding disorder associated with high risk for intracranial hemorrhage, requiring complicated neurosurgical interventions. Perioperative management is based on quick factor replacement therapy, control of hemostasis, and deciding whether surgery will be beneficial. Methods: We report the case of a 49-year-old male with severe hemophilia A who had purulent secernation via a skin fistula as a late complication of decompressive craniectomy for epidural hematoma at younger age. Results: Revision surgery was successfully managed with perioperative administration of clotting factor VIII, and the patient showed indications of titanium cranioplasty. Conclusions: A direct preoperative preparation prior to surgery in a postoperative period with controlled hemostasis has been shown to reduce hemorrhagic complications in hemophilic patients, increasing the quality of life and significant neurological complications.